ERROR ANALYSIS IN THE TRAVEL WRITING TEXTS MADE BY THE STUDENTS OF STUDY PROGRAM OF ENGLISH - AGUSTINA, VIKA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords:  Error, Error Analysis, Surface Strategy Taxonomy, Travel WritingError reflects the lack of knowledge of the learner. The process of language learning is the time when the language learners make mistakes or error. In writing, the learner must avoid producing error in order to compose a goodwriting. Regarding the errors made by the language learners, this study wasconducted to answer: (1) what kinds of errors in surface strategy taxonomy aremade by the fifth semester students of English Study Program in producing theirtravel writing texts? and (2) what is the dominant type of error made by the fifthsemester students of English Study Program in producing their travel writingtexts?This study used qualitative approach in relation to the use of clear and systematic description about the phenomena being studied. It is to describe thedata obtained from English Department students’ literary work in the form ofwritten texts.This analysis finds the grammatical errors which are made in the travel writing produced by the fifth semester students of Study Program of English Department of Universitas Brawijaya based on surface strategy taxonomy theory which consists of four types of errors. They are (1) omission, (2) addition, (3) misformation and (4) misordering. Mostly the errors occuring in misformation are in the use of tense form. Secondly, the errors are in omission of noun/verbinflection. The next error, there are many clauses that contain unnecessary phrase added there. According to the researcher, the cause why the students made such errors is that because of their limited vocabulary, so they just put the words they knew without concerning to any caution of inappropriate words or meaning.The researcher suggests the students who are interested in conducting thesame field should fill the gaps and lacks that cannot be fulfilled by this study. She also suggests that the next researcher should complete their future analysis, especially on an error analysis by using other theories than Dulay’s theory.